1999
DOI: 10.1006/expr.1999.4424
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum: Population Genetic Analysis by Multilocus Enzyme Electrophoresis and Other Molecular Markers

Abstract: Population genetic definitely in the other Burkina Faso population. However, no linkage disequilibrium is detected in the Congo population with the molecular analysis by multilocus enzyme electrophoresis and other molecular markers. Experimental Parasitology 92, 232-238. The population assays. We failed to detect any nonrandom association between the different kinds of genetic markers; that is, MLEE with RAPD or RFLP, structure of Plasmodium falciparum, the agent of malignant malaria, is uncertain. We have ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
11
1
1
Order By: Relevance
“…The inference followed that "uniparental and biparental lineages may coexist within this species, for which a sexual cycle has been a classical notion" (Tibayrenc et al, 1990). Although this inference was corroborated by further studies (Ben Abderrazak et al, 1999;Urdaneta et al, 2001), it resulted in a vehement outcry (Dye et al, 1990;Walliker, 1991;Walliker et al, 1990). Our proposal was widely rejected.…”
Section: Initial Proposalsmentioning
confidence: 81%
“…The inference followed that "uniparental and biparental lineages may coexist within this species, for which a sexual cycle has been a classical notion" (Tibayrenc et al, 1990). Although this inference was corroborated by further studies (Ben Abderrazak et al, 1999;Urdaneta et al, 2001), it resulted in a vehement outcry (Dye et al, 1990;Walliker, 1991;Walliker et al, 1990). Our proposal was widely rejected.…”
Section: Initial Proposalsmentioning
confidence: 81%
“…The extent of cross-fertilization and panmixia relative to clonal reproduction in P. falciparum has indeed been the subject of considerable debate during the last decade (13,19,(26)(27)(28)(29)(30). The current consensus is that this parasite species displays a range of population structures associated with the levels of transmission intensity (13).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the results do not imply that recombination is effectively breaking haplotype structure. Indeed, strong linkage disequilibrium has been observed between physically unlinked markers (29), as well as significant deficit of heterozygous oocysts in populations of Tanzania (18) and Papua New Guinea (8), where overall inbreeding coefficients have been estimated at 0.34 and 0.90, respectively (12). Anderson et al (5) observed significant linkage disequilibrium among 12 microsatellite loci in all localities with low infectivity and in two of five populations from regions with high transmission frequencies.…”
Section: Discussionmentioning
confidence: 99%